2014
DOI: 10.1039/c4nr01526f
|View full text |Cite
|
Sign up to set email alerts
|

Metal-induced self-assembly of peroxiredoxin as a tool for sorting ultrasmall gold nanoparticles into one-dimensional clusters

Abstract: Nanomanipulation of matter to create responsive, ordered materials still remains extremely challenging. Supramolecular chemistry has inspired new strategies by which such nanomaterials can be synthesized step by step by exploiting the self-recognition properties of molecules. In this work, the ring-shaped architecture of the 2-Cys peroxiredoxin I protein from Schistosoma mansoni, engineered to have metal ion-binding sites, is used as a template to build up 1D nanoscopic structures through metal-induced self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…In addition to a putative biomedical relevance, the ability of Prxs to form such organized supramolecular HMW assemblies in a switch-like fashion makes them an attractive candidate for application in protein nanotechnology (Phillips et al, 2014). For instance, Ardini et al (2014) demonstrated the use of Prx tubes as nano-peapods for ultra-small gold particles, which could be useful as nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a putative biomedical relevance, the ability of Prxs to form such organized supramolecular HMW assemblies in a switch-like fashion makes them an attractive candidate for application in protein nanotechnology (Phillips et al, 2014). For instance, Ardini et al (2014) demonstrated the use of Prx tubes as nano-peapods for ultra-small gold particles, which could be useful as nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on creating protein assemblies has been largely centered around amyloid fibers [25][26][27][28][29] but has recently also involved native protein structures [30][31][32] with ring shaped proteins emerging as a commonly used self-assembling feature. [33][34][35][36][37] Recent work has established methods to post functionalize assembled structures, 38,39 an important step towards applications based on protein nanostructures. There is intense interest in "one-dimensional nanostructures".…”
Section: Introductionmentioning
confidence: 99%
“…We seek here to harness the unique features of a protein, Lsmα from Methanobacterium thermoautotrophicum, which was selected for its thermostability and ability to self-assemble into a heptameric ring. 40,41 Proteins like Lsmα and peroxiredoxin 36 self-assemble into robust doughnuts whose pore size can be tuned specifically to encapsulate metal complexes or nanoparticles 37 and then assemble further into tunnels to create magnetic, electrical or optical nanorods. Accordingly, we have explored the possibility of using self-assembled block copolymers as scaffolds to create regular arrays of such doughnut tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Prxs belong to an abundant family of peroxide-dependent antioxidant enzymes within cells (Perkins, Nelson, Parsonage, Poole, & Karplus, 2015;Rhee, Chae, & Kim, 2005). Although Prxs can be found as CP dimers in solution, decameric toroidal capsids with an approximate outer diameter of 13 nm, an inner pore of 6 nm, and a height of 4 nm are more commonly found (Ardini et al, 2014;Domigan et al, 2017;Jang et al, 2004) (Figure 1g). Furthermore, larger aggregates and higherorder complexes such as toroid stacks or spherical cages are naturally found under reducing conditions (Lowther & Haynes, 2011;Phillips et al, 2014).…”
Section: Peroxiredoxinmentioning
confidence: 99%
“…Copyright 2018 American Chemical Society, Medalsy et al (2008). Copyright 2008 American Chemical Society, Ardini et al (2014). Copyright 2014 Royal Society of Chemistry, and Sendai et al (2013).…”
Section: Coordination Bonding Via Metal-ligand Interactionsmentioning
confidence: 99%